Backpacking through Bedlam - McGuire, Seanan (McGuire, Seanan. InCryptid novel, 2023)
"The fast-paced InCryptid urban fantasy series returns to the mishaps of the Price family, eccentric cryptozoologists who safeguard the world of magical creatures living in secret among humans. With the wonders of the cosmos open to them, Thomas and Alice Price have returned to the most exciting place they could think of: home. But it's been a while, and they're out of step. What's more, trouble is brewing in New York, trouble that threatens both their family and the fragile peace they've been maintaining for generations. Time to get weird"--